The mikado - Sullivan, Arthur 1842-1900 (Opus Arte, 2006)
Registratie van Engelse operette van Gilbert & Sullivan.
Interpr.: Anne-Maree McDonald, Yum-Yum. Peter Cousens, Nanki-Poo. Robert Eddie, The Mikado. Heather Begg, Katisha. Graeme Ewer, Ko-Ko. Gregory Yurisich, Pooh-Bah. Jennifer Bermingham, Pitti-Sing. The Elizabethan Sydney Orchestra. Andrew Greene [Dir.] Christopher Renshaw [Regie]. - Aufn.: Sydney Opera House 1987. - Teilw. in der Kassette: The Gilbert & Sullivan collection : 4 DVD set
Keywords: Sullivan, Arthur -- 1842-1900 -- The mikado; Oper; Prinz; Verfilmung; Japan; Film; DVD-Video